PENANGANAN ABRASI PANTAI DESA SEI RAJA KABUPATEN SUKAMARA KALIMANTAN TENGAH - Mustofa Kamal Aziz; Seruni Adidar Lesmi; Sumbogo Pranoto; Priyo Nugroho Parmantoro (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
The problems of the coastal area in Sei Raja Beach were retreat of the coastline, sedimentation in river mouth of Raja River, destruction of existing shore protection structure such as groin and jetty which was caused of wave. The objective of the final project is to model and to design the right shore structures to protect the shore from abrasion in Sei Raja Beach. The area which planned is around 3,1 km include the river mouth of Raja River. The analysis result of waverose shows that dominant wave comes from the south. It is about 68,61% from the data in 23 years. The current movement pattern and tide is simulated by the SMS V.10 program (Surface Water Modelling System). The prediction of coastline changed is simulated by GENESIS (Generalized Model for Simulating Shoreline Change) with wave input per-hour for a year. The shoreline protection is analyzed based on function and economical value. The combination between revetment, jetty, groin and breakwater is chosen to protect the shore of Sei Raja. The western revetment are designed along 522 m and the eastern revetment are designed along 651 m. The western revetment and the eastern revetment are made of concrete cube for armour layer and crushed stone for core layer. Twins jetty which made of concrete cubes for armour layer and crushed stones for secondary and core layer are built with a length of 150 m. The groin is planed on the west side with the length of 75 m. The groin is used of crushed stones for armour and core layer. The existing breakwater is rehabilitated by adding concrete cubes.